Development of Case-Based Learning Modules on Wave Topics to Improve Students' Cognitive Abilities - Nihayatu Zein; Dwi Nanto; Kinkin Suartini (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
Students' cognitive abilities in physics learning, particularly on wave topics, still need to be improved through more contextual and innovative instructional materials. Therefore, this research aims to develop a physics learning module on wave material in accordance with Case-Based Learning (CBL). In addition, it also examines its feasibility, experience and effectiveness in improving students' cognitive abilities. This research uses the Research and Development (R&D) method using 3D models, limited to the definition, design, and development stage where 12th grade students are the subject of learning. The feasibility of the developed modules was evaluated using the Learning Object Review Instrument (LORI), while the practicality was assessed through the User Experience Questionnaire (UEQ). The effectiveness of the module was measured using N-Gain analysis based on pretest and posttest results. The results show that the developed CBL-based modules are categorized as very feasible and provide a positive user experience. In addition, the N-Gain analysis showed an improvement in the cognitive abilities of the learners, with most of the learners achieving scores in the medium category. These findings suggest that CBL-based physics learning modules on wave materials are quite effective and suitable for use as an alternative instructional resource to improve the quality of physics learning in high school.